HNF1B nephropathy has a slow-progressive phenotype in childhood: with the exception of very early onset cases : results of the German Multicenter HNF1B Childhood Registry - Okorn, Christine; Tönshoff, Burkhard (Pediatric nephrology, 2019)
BackgroundHNF1B gene mutations are an important cause of bilateral (cystic) dysplasia in children, complicated by chronic renal insufficiency. The clinical variability, the absence of genotype-phenotype correlations, and limited long-term data render counseling of affected families difficult.MethodsLongitudinal data of 62 children probands with genetically proven HNF1B nephropathy was obtained in a multicenter approach. Genetic family cascade screening was performed in 30/62 cases.ResultsEighty-seven percent of patients had bilateral dysplasia, 74% visible bilateral, and 16% unilateral renal cysts at the end of observation. Cyst development was non-progressive in 72% with a mean glomerular filtration rate (GFR) loss of − 0.33 ml/min/1.73m2 per year (± 8.9). In patients with an increase in cyst number, the annual GFR reduction was − 2.8 ml/min/1.73m2 (± 13.2), in the total cohort − 1.0 ml/min/1.73m2 (±10.3). A subset of HNF1B patients differs from this group and develops end stage renal disease (ESRD) at very early ages < 2 years. Hyperuricemia (37%) was a frequent finding at young age (median 1 year), whereas hypomagnesemia (24%), elevated liver enzymes (21%), and hyperglycemia (8%) showed an increased incidence in the teenaged child. Genetic analysis revealed no genotype-phenotype correlations but a significant parent-of-origin effect with a preponderance of 81% of maternal inheritance in dominant cases.ConclusionsIn most children, HNF1B nephropathy has a non-progressive course of cyst development and a slow-progressive course of kidney function. A subgroup of patients developed ESRD at very young age < 2 years requiring special medical attention. The parent-of-origin effect suggests an influence of epigenetic modifiers in HNF1B disease.